A 2D numerical study on suppressing liquid sloshing using a submerged cylinder. (1st July 2017) - Iranmanesh, A.; Passandideh-Fard, M.
Abstract: In this paper, a two-dimensional numerical model is proposed to study the effect of a submerged cylinder on suppressing liquid sloshing in a moving container. The continuity and Navier-Stokes equations are solved along with an equation for the free surface advection. The Volume of Fluid (VOF) method is used to simulate the free-surface deformation. The numerical model for liquid sloshing is validated with the available experimental, and numerical results in the literature. The results of simulations are in good agreement with those of the measurements. Two scenarios for the liquid sloshing are studied. In the first case, the liquid container is excited with a Constant Acceleration (CA). For the second case, the container is moved with a Single Oscillatory Excitation (SOE). The suppression rate of total kinetic energy of sloshing with the submerged cylinder for two scenarios are calculated and compared to the cases with free sloshing with no cylinder. For the first and second scenarios, using the submerged cylinder reduced the total kinetic energy of sloshing by 26.58% and 71.6%, respectively. Therefore, the effect of submerged cylinder on suppressing the liquid sloshing is more pronounced in the second scenario where the container is excited with the SOE. Highlights: A 2D numerical approach is presented to simulate the solid-liquid interaction. The free surface deformation is modelled using the VOF method. The feasibility of a submerged cylinder in reducing the fluid sloshing is studied. The results of sloshing with the CA and SOE are compared. The effects of various parameters in mitigating the liquid sloshing are evaluated.